2012
DOI: 10.1002/adfm.201103106
|View full text |Cite
|
Sign up to set email alerts
|

Colossal Thermoelectric Power Factor in K7/8RhO2

Abstract: We discuss the thermoelectric and optical properties of layered KxRhO2 (x = 1/2 and 7/8) in terms of the electronic structure determined by first principles calculations as well as Boltzmann transport theory. Our optimized lattice constants differ significantly from the experiment, but result in optical and transport properties close to the experiment. The main contribution to the optical spectra are due to intra and inter-band transitions between the Rh 4d and O 2p states. We find a similar power factor for p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 48 publications
(48 reference statements)
2
21
0
Order By: Relevance
“…In K x RhO 2 , similar e g pockets are also predicted [ Fig. 4(b)] [27]. However, our data reveal that the topmost e g dispersion is essentially flat near K at 0.25 eV below E F .…”
Section: -2supporting
confidence: 89%
See 2 more Smart Citations
“…In K x RhO 2 , similar e g pockets are also predicted [ Fig. 4(b)] [27]. However, our data reveal that the topmost e g dispersion is essentially flat near K at 0.25 eV below E F .…”
Section: -2supporting
confidence: 89%
“…However, our data reveal that the topmost e g dispersion is essentially flat near K at 0.25 eV below E F . Interestingly, the total occupied bandwidth of the t 2g complex is only renormalized by a factor of 1.15 from the DFT value [27], suggesting a weak electron correlation. Therefore, in K x RhO 2 , the sinking of the e g pockets without strong electron correlation provides new opportunities to test the existing theories.…”
Section: -2mentioning
confidence: 94%
See 1 more Smart Citation
“…6 A giant thermoelectric effect was predicted in K 7/8 RhO 2 by the first principles calculations. 7 However, many important problems remain unresolved with regard to the K x RhO 2 system. For example, how does the thermopower of K Can there be superconductivity in the water-intercalated K x RhO 2 ?…”
Section: Introductionmentioning
confidence: 99%
“…4 The K content also affects strongly the crystal structure which in turn modifies the thermoelectric, electrical, and magnetic transport properties. Saeed et al 5 calculated the electronic structure of K x RhO 2 (x = 0.5 and x = 7/8) showing that K x RhO 2 is a potential thermoelectric material. Further studies confirmed that K x RhO 2 (x = 0.49 and 0.63) single crystals exhibits a moderate Seebeck coefficient at room temperature.…”
mentioning
confidence: 99%